Problems of Fishermen in Nellore District of Andhra Pradesh - Mallikarjunaiah, U.; Sudarsan, K. (Prabandhan: Indian Journal of Management, 2012)
The fishery sector has witnessed serious crises during the last decade owing to its limitations to adjust to the changing environment. It is caught in a net of interrelated problems like lack of finance, lack of storage facilities and quick delivery of input, lack of ice-plants, lack of awareness of market information, uncertain quality of fish, faulty measurement system, lack of market infrastructure, imbalance between demand and supply of fish, low level of education among fishermen, and lack of availability of other and alternative profitable occupation for them, inadequate income and relatively high level of expenditure, extremes of climate, natural calamities like floods and draught, the tsunami, lack of appropriate policy measures, weak organizational structure of fishermen cooperatives, failure of the cooperative system, lack of transportation facilities, and the like. An attempt has been made in this article to enquire into the problems confronted by fishermen in Nellore District of Andhra Pradesh. The primary data was collected from a representative sample of fishermen cooperatives in the areas of finance, production, marketing, raw material and infrastructure facilities, etc. Further, it offers some suggestions for consideration in the light of the observations made in the present study of the working of fishermen co-operatives in Nellore district. The research work was conducted during August 2010 to February 2011.